Pathophysiological mechanisms, multidimensional diagnostics and modern therapies of pruritus in pancreatic cancer: review and perspectives - Jagienka Agata Włodyka; Urszula Zelik; Maria Przygoda; Wiktoria Domino; Gabriela Trestka; Sabina Adamczyk; Kamila Stępień; Joanna Śnieżna; Wojciech Florczak; Karol Dzwonnik; Jakub Dziewic (Quality in Sport)
Introduction and purpose: Pruritus is a subjective, unpleasant sensation that leads to scratching and significantly impacts the quality of life of patients. In pancreatic cancer, its etiology is multifactorial. It can result from various mechanisms, with a particular emphasis on cholestasis, which represents the most important and frequent cause of this symptom, as well as paraneoplastic processes, neuropathic mechanisms, or side effects of therapy. The aim of this study is to analyze the mechanisms responsible for pruritus in pancreatic cancer, discuss diagnostic challenges, and review the available therapeutic methods and challenges, including bile duct decompression, the use of autotaxin inhibitors, opioid receptor antagonists, and SSRI drugs. The article is based on an analysis of the available scientific literature and cited sources.